UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI BERBEDA ITU INDAH DI KELAS III SEKOLAH MIS AL-BASHIRAH - Permadani, Indah; Yarshal, Dinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the learning motivation of third-grade students at MIS Al-Bashirah in the Pancasila Education subject, "Different is Beautiful," through the use of interactive learning media. The background of this study is low student learning motivation, which impacts student participation and lack of interest in conventional learning processes.This study used the Classroom Action Research (CAR) method. The subjects were 22 third-grade students at MIS Al-Bashirah. Data were collected through observation, interviews, and d1ocumentation. The results showed that the use of interactive learning media successfully increased student learning motivation. This was evident in the increase in student motivation indicators from 30% in the pre-cycle, 56% in the first cycle, 72% in the second cycle, and 85% in the third cycle. Observation sheets showed improvements in student comfort in learning, active participation, clear interest in the material, and discipline during learning. These improvements demonstrate that interactive learning media are effective in creating a more engaging learning environment and fostering student motivation. It was concluded that interactive learning media can be an effective solution for increasing student learning motivation in Pancasila Education. It is recommended that teachers integrate interactive learning media into their teaching practices to create more innovative and meaningful learning experiences.